Electronic Publishing: The Unfolding Revolution - Rao, Aluri (DESIDOC Journal of Library & Information Technology, 2002)
The author gives an overview of electronic publishing and enumerates the technological advances that has led to its growth. He discusses the advantages offered by the technology to researchers and other library users. The disadvantages to the publishers and libraries/information centres are also discussed and the effect of this technology on the policies and processes in the library are presented. http://dx.doi.org/10.14429/dbit.16.1.3168